Regioselective Radical Arylation of 3-Hydroxypyridines - Fürst, Michael; Bock, Leonard; Heinrich, Markus (Journal of Organic Chemistry, 2016)
The titanium(III)-mediated radical arylation of 3-hydroxypyridines was found to proceed with high regioselectivity for the 2-position. Using aryldiazonium chlorides, which were prepared from the corresponding anilines, as aryl radical sources, a range of 3-hydroxy-2-phenylpyridines were obtained in moderate to good yields under simple reaction conditions. Reactions of ortho-carboxylic ester substituted phenyldiazonium salts directly provided tricyclic benzopyranopyridinones.